2014
DOI: 10.1186/gb-2014-15-3-r49
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of 5-hydroxymethylcytosine and 5-methylcytosine at base resolution in the human brain

Abstract: Background5-methylcytosine (mC) can be oxidized by the tet methylcytosine dioxygenase (Tet) family of enzymes to 5-hydroxymethylcytosine (hmC), which is an intermediate of mC demethylation and may also be a stable epigenetic modification that influences chromatin structure. hmC is particularly abundant in mammalian brains but its function is currently unknown. A high-resolution hydroxymethylome map is required to fully understand the function of hmC in the human brain.ResultsWe present genome-wide and single-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
231
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(268 citation statements)
references
References 48 publications
33
231
1
3
Order By: Relevance
“…In addition to specific sites of intragenic enrichment for hmCG, an accumulation of hmCG occurs broadly across intergenic regions of the neuronal genome. Thus, in stark contrast to other cell types, such as ES cells, in which hmCG is localized primarily to active regulatory elements, in neurons, even intergenic regions contain substantial levels of hmCG (20-30%) (8,33).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In addition to specific sites of intragenic enrichment for hmCG, an accumulation of hmCG occurs broadly across intergenic regions of the neuronal genome. Thus, in stark contrast to other cell types, such as ES cells, in which hmCG is localized primarily to active regulatory elements, in neurons, even intergenic regions contain substantial levels of hmCG (20-30%) (8,33).…”
mentioning
confidence: 88%
“…Although hmCG is present at appreciable levels in neurons, TLC and genome-wide bisulfite sequencing analyses conducted to date suggest that hmCA, if it exists, is present in the neuronal genome at low levels (8,29,33). Thus, oxidative conversion of mC to hmC may primarily influence the distribution of MeCP2 molecules in neuronal chromatin by decreasing the binding affinity of MeCP2 at preexisting mCG sites.…”
Section: Binding Of Mecp2 To the Brain-specific Methylomementioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have reported associations between development and aging and DNA methylation profiles in different brain regions, blood, muscle, saliva, and other tissues, including both cross-sectional and longitudinal analyses [89][90][91][92][93][94]. Importantly, these types of studies have not all accounted for the confounding effects of having samples with varying cellular compositions [95].…”
Section: Development and Agingmentioning
confidence: 99%
“…Point mutation in a primate-specific repeat (L1PA8) within an Alu element, which is embedded in a brain expressed lncRNA, mediates disease [23] Rett syndrome MeCP2 represses L1 retrotransposition in neuronal cells and, in reprogrammed cells from Rett syndrome patient tissues, L1 activity is increased [47] Schizophrenia L1 copy number is increased in neurons from patient-derived prefrontal cortex specimens, and brain-specific L1 insertions seem to preferentially target genes involved in synaptic function or linked to schizophrenia [46] ATM = ataxia telangiectasia mutated; SVA = SINE-VNTR-Alu; 3′-UTR = 3′-untranslated region; lncRNA = long noncoding RNA; MeCP2 = methylCpG-binding protein 2; L1 = long interspersed element 1 during development and aging [89][90][91][92][93][94]. Moreover, it is notable that methylation marks measured in easily accessible peripheral tissues, such as blood, can serve as reliable surrogates for those present in brain for certain subsets of genes [89].…”
Section: Diseasementioning
confidence: 99%